Evaluation of treatment for camptodactyly: retrospective analysis on 40 fingers, - Saulo Fontes Almeida; Anderson Vieira Monteiro; Rúbia Carla da Silva Lanes (Revista Brasileira de Ortopedia, 2014)
OBJECTIVE: to retrospectively assess the results from cases treated in the hand surgery service, starting from a preestablished protocol; and to conduct a critical analysis on the results achieved, with separation of the cases into their respective subgroups.METHODS: twenty-three patients and a total of 40 fingers were evaluated between January 2004 and December 2011. We correlated the altered anatomical structures found in the cases that underwent the surgical procedure and its results, with regard to both conservative and surgical treatment, emphasizing the main indications.RESULTS: the results were analyzed using the Sierget method of the Mayo Clinic.CONCLUSION: we observed that the cases of camptodactyly of the little finger alone in the flex-ible form (>60◦) that underwent surgical treatment uniformly presented excellent results. In the rigid forms, our observations indicated that there were benefits comprising gains of extension and correction of the deformity. However, the range of motion with active flexion in the proximal interphalangeal joint was always partial. With evolution over time, some cases presented some loss of the gain previously achieved, which corroborates the need for continual vigilance during the follow-up, with systematic use of braces until the final phase of skeletal growth.